2020
DOI: 10.1016/j.nicl.2020.102400
|View full text |Cite
|
Sign up to set email alerts
|

Multiple markers contribute to risk of progression from normal to mild cognitive impairment

Abstract: Highlights We examined the markers that optimally predict progression from normal to MCI. A LASSO Cox model was used to determine the minimum set of markers. Entorhinal thickness, Aβ burden, default network connectivity, and hippocampal volume predicted progression. These markers may enhance risk stratification in clinically normal adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 63 publications
2
8
0
Order By: Relevance
“…Kaplan-Meier curves and Cox proportional hazards regression results for lateral orbitofrontal cMD (high/low groups) predicting (A) progression to MCI, (B) progression to CDR = 0.5. cMD cortical mean diffusivity, CTh cortical thickness, PIB_status Aβ+ vs. Aβ−; "High cMD" = top-tertile cMD values ("Low cMD", otherwise). combination, to predict short-term cognitive decline and clinical progression [44,49]. In line with previous observations [8], we found that PIB status was a strong predictor of clinical progression to MCI or CDR = 0.5 during~3.5 years follow-up.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Kaplan-Meier curves and Cox proportional hazards regression results for lateral orbitofrontal cMD (high/low groups) predicting (A) progression to MCI, (B) progression to CDR = 0.5. cMD cortical mean diffusivity, CTh cortical thickness, PIB_status Aβ+ vs. Aβ−; "High cMD" = top-tertile cMD values ("Low cMD", otherwise). combination, to predict short-term cognitive decline and clinical progression [44,49]. In line with previous observations [8], we found that PIB status was a strong predictor of clinical progression to MCI or CDR = 0.5 during~3.5 years follow-up.…”
Section: Discussionsupporting
confidence: 91%
“…Timeto-event was defined as years from baseline to the first follow-up visit when a participant was diagnosed as mild cognitive impairment (MCI). For comparison, separate survival models were set-up using progression from CDR = 0 to 0.5 as a subtler definition of clinical progression [44]. We applied multivariable Cox proportional hazards regression models to estimate hazard ratios (HRs) with 95% confidence intervals (CI) to investigate whether dichotomous regional cMD ("high cMD" defined as top-tertile cMD; "low cMD" otherwise) predicts subsequent diagnosis of MCI/AD, or progression to CDR = 0.5.…”
Section: Prediction Of Clinical Outcomesmentioning
confidence: 99%
“…Our MRI findings are in agreement with a recent study ( Rabin, 2020 ) that found reduced entorhinal thickness and smaller hippocampal volume predicted conversion to MCI within 5 years. However, we distinguished baseline differences in these markers in a shorter time interval (within a year).…”
Section: Discussionsupporting
confidence: 93%
“…Twenty-six studies (the first published in 2012) used resting-state MRI (rsMRI): we did not identify any studies using task-based MRI. All but four studies (Hojjati et al 2017;2018;Hojjati, Ebrahimzadeh, and Babajani-Feremi 2019;Rabin et al 2020) focused on diagnosis and the majority (20/26) used ADNI data, either as the primary dataset or as a replication dataset. Graph measures were often used to summarize network characteristics.…”
Section: Functional Mrimentioning
confidence: 99%
“…Around half of studies leveraged structural MRI alone (132/252) and those making use of multiple modalities (49/252) often used sMRI and PET (35/49) together. It is only since 2020 that studies incorporating three or more different modalities have begun to appear (T. R de Vos et al 2020;Rabin et al 2020…”
mentioning
confidence: 99%